Preparing Students for Community Pharmacy Practice During a Drug Information Advanced Practice Experience - Lauderdale, Stacy A. (American Journal of Pharmaceutical Education, 2007)
OBJECTIVE: To determine whether students completing an advanced pharmacy practice experience (APPE) at an academic-affiliated drug information center received questions similar to those received by pharmacists practicing in community settings. METHODS: Graduates of Samford University McWhorter School of Pharmacy residing in Southeastern states were surveyed via US mail to determine the characteristics of inquiries received from health care providers and the public in community practice. Survey results were compared to inquiries received at Samford University Global Drug Information Center (SUGDIS). RESULTS: The response rate to the survey of graduates was 36% (268 of 738 surveys). Respondents identified nonprescription drugs (65%), adverse drug reactions (62.7%), and drug interactions (62.4%) as the top 3 types of questions answered routinely in community practice, while drug therapy (13.9%), dosing (10.2%), and adverse drug reactions (6.5%) were the 3 types of questions most commonly answered at SUGDIS. The most common resources used to answer questions in the community and SUGDIS were Drug Facts and Comparisons and specialty references, respectively. CONCLUSIONS: Differences were noted in types of questions received, expected speed of response, and reference utilization. As a result, activities were incorporated into the drug information APPE to address the disparities noted in the study.